Balance sheet recession as the 'other half' of macroeconomics - Richard C. Koo (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
Once every several decades, the private sector loses its mind in a bubble, leverages itself up to the hilt, and is forced into debt minimization in order to remove its debt overhang following the crash. When the private sector as a whole is deleveraging, even at record low interest rates, monetary policy is largely ineffective while fiscal policy becomes absolutely essential in keeping both the economy and money supply from shrinking. The superior effectiveness of monetary policy during private sector profit maximization and of fiscal policy during private sector debt minimization indicates that the latter was the long-overlooked 'other half' of macroeconomics.
Keywords: D21; E32; E51; E62; 330; other half' of macroeconomics; Yin and Yang economic cycles; micro-foundation of macroeconomics; unborrowed savings; dual problem of economics; debt minimization; balance sheet recession